Guardian's Responsibilty For The Welfare of Children In Marriage: A Study According to Islamic Law - Redwan Yasin; Nurul Hidayat Abdul Rahman; Sayuti Ab. Ghani; Mohamed Belal (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, Volume 12 Issue 3 Page (778–789)